Effects of nitrogen supply methods on fate of nitrogen in maize under alternate partial root-zone irrigation - Qi, Dongliang; Hu, Tiantian; Song, Xue (International Journal of Agricultural and Biological Engineering, 2020)
Partial root-zone irrigation (PRI) has been practiced worldwide, but little information is available on nitrogen (N) supply methods influence on fate of applied N fertilizer for crop production under PRI. A field experiment was conducted to investigate effect of N supply methods on the uptake, residual, and loss of applied N fertilizer in maize (Zea mays L.) under alternate PRI at Wuwei, northwest China in 2014. 15N-labeled urea was used as N fertilizer. Two irrigation methods included alternate furrow irrigation (AI) and conventional furrow irrigation (CI). Two N fertilizer supply methods included conventional N supply (CN) and alternate N supply (AN), were applied in combination with each irrigation method. Grain yield, root length density (RLD), N uptake by maize at the maturity stage, and atom % of 15N excess, residual 15N and residual NO3-N in the 0-100 cm soil layer after maize harvest were determined. Results shown that compared to CI coupled with CN, AI coupled with AN or CN significantly increased the grain yield, harvest index, RLD, N uptake by maize, 15N accumulation in grain, atom % of 15N excess in the 0-60 cm soil layer, the residual 15N and 15N uptake rates; but significantly decreased the residual NO3-N in the 0-100 cm soil layers and 15N loss rate. Moreover, the synchronized rather than separation supply of N fertilizer and water enhanced the most above parameters under AI. 15N uptake rate was positively correlated with RLD in the 0-40 cm soil layer, suggesting that the enhanced RLD contributed to the improved 15N uptake rate. Therefore, alternate furrow irrigation coupled with conventional or alternate nitrogen supply (synchronized supply of N fertilizer and water) could help improve 15N uptake rate and reduce the 15N loss rate.Keywords: 15N-labeled technology, root length density, nitrogen fertilizer fate, nitrogen management, residual nitrogenDOI: 10.25165/j.ijabe.20201303.5287Citation: Qi D L, Hu T T, Song X. Effects of nitrogen supply methods on fate of nitrogen in maize under alternate partial root-zone irrigation. Int J Agric & Biol Eng, 2020; 13(3): 129–135.